2010
DOI: 10.15835/nsb244690
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Temperatures and Durations on the Dormancy Breaking of Black Locust (Robinia pseudoacacia L.) and Honey Locust (Gleditsia triacanthos L.) Seeds

Abstract: In order to break seed dormancy, different temperatures (20, 30, 40, 50, 60, 70, 80 and 90 o C) and durations (10, 20 and 30 minutes) were applied to black locust (Robinia pseudoacacia L.) and honey locust (Gleditsia triacanthos L.) seeds, in the Seed Laboratory of Dicle University -Faculty of Agriculture in 2009. According to the research results, the highest germination rate for black locust seeds was obtained in the case of 90 o C for 30 minutes pre-treatment (94.5%), whilst the lowest value was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The needle puncture or blade cut is frequently cited in the literature as effective in breaking physical dormancy of black locust, Fabaceae or other physically dormant seeds (Singh et al ., 1991; Funes and Venier, 2006; Masaka and Yamada, 2009; Cierjacks et al ., 2013; Abudureheman et al ., 2014; Giuliani et al ., 2015), so that it can be used as a reference method. The absence of germination following dry-heat treatments contradicted previous studies that reported 90–94% germination (Masaka and Yamada, 2009; Basbag et al ., 2010). Hot water soaking is proposed by forest managers to break physical dormancy (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The needle puncture or blade cut is frequently cited in the literature as effective in breaking physical dormancy of black locust, Fabaceae or other physically dormant seeds (Singh et al ., 1991; Funes and Venier, 2006; Masaka and Yamada, 2009; Cierjacks et al ., 2013; Abudureheman et al ., 2014; Giuliani et al ., 2015), so that it can be used as a reference method. The absence of germination following dry-heat treatments contradicted previous studies that reported 90–94% germination (Masaka and Yamada, 2009; Basbag et al ., 2010). Hot water soaking is proposed by forest managers to break physical dormancy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Seeds were stored in paper bags in a cold room between 0 and 5°C (Bonner and Karrfalt, 2008; Cierjacks et al ., 2013). Two hundred and ten seeds from one tree of the Gabarnac population (Gironde, France) were used to test seven dormancy-breaking treatments, with 30 seeds per treatment: puncturing (P), consisting of making one pin puncture in the seed coat, using a needle; dry-heat (Basbag et al ., 2010) was applied by placing seeds in a Petri dish in an oven at 90°C for 20 and 30 min (H20, H30); imbibition by soaking in water (W) was performed in one cycle, placing seeds in nearly boiling water at 95°C (Turner and Dixon, 2009) and letting them cool for 15 h; finally we tested a novel sanding treatment (Fig. 1) using an automated grinder (2010 Geno/Grinder, SPEX SamplePrep, Metuchen, NJ, USA) that allows shaking of tubes controlling both intensity and duration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that R . pseudoacacia seeds present dormancy [ 66 ], we assessed germination with one set of untreated seeds and another set of scarified seeds (1 minute in 90°C water + 24h soaked; [ 67 ]) to estimate the maximum potential germination. A seed was considered germinated when radicle emergence was observed.…”
Section: Methodsmentioning
confidence: 99%
“…Given that R. pseudoacacia seeds present dormancy [19], we used two sets of seeds for germination tests, one untreated and the other pretreated, to break dormancy. Based on previous experiments and studies [54], the best pretreatment consisted of scarifying them with boiling water (90 ∘ C) for one minute, subsequently removing them from heat and keeping them in water for 24 h. We did not pretreat F. angustifolia seeds because at the time of collection they had already overwintered in the crowns, and therefore they had naturally undergone cold stratification, which is considered to break dormancy in this species [55]. Petri dishes were randomly distributed in the germination chamber and rotated every 3-4 days to avoid position effects.…”
Section: Experimental Designmentioning
confidence: 99%